Factors influencing e-filing usage among malaysian taxpayers: does tax knowledge matters? - Affiza Mohd Tallaha,; Zaleha Abdul Shukor,; Norul Syuhada Abu Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2014)
The present study investigates whether tax knowledge influences the level of intention of individual taxpayers to use E-filing after four years of its implementation (2006 to 2009) in Malaysia. The study examines factors that might influence taxpayers’ level of intention to use E-filing based upon the theoretical framework of technology acceptance model (TAM); the theory of planned behavior (TPB); and the concept of tax knowledge. The survey was conducted on 228 individual taxpayers within the city of Kuala Lumpur in 2011 and shows that respondents have a high level of intention to use E-filing (4.34 out of 5). Empirical findings show that perceived usefulness, perceived ease of use and perceived subjective norms are positively associated, but perception on behavioral control and tax knowledge are not significantly associated with taxpayers’ intention to use E-filing. Since the Inland Revenue Board Malaysia (IRBM) is currently promoting the use of E-filing, the results may assist the IRBM to plan a more effective strategy of promoting E-filing usage among individual taxpayers in Malaysia.